2019
DOI: 10.1021/acsomega.8b03615
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of Hierarchical AgNP-Loaded MXene/Fe3O4/Polymer Nanocomposites by Electrospinning with Enhanced Catalytic Performance for Wastewater Treatment

Abstract: MXene as a kind of two-dimensional nanomaterial has aroused people’s strong research interest because of its excellent properties. In the present study, we introduced a new poly(vinyl alcohol)/poly(acrylic acid)/Fe 3 O 4 /MXene@Ag nanoparticle composite film fabricated by electrospinning and heat treatment as well as self-reduction reaction process. The obtained composite films showed high self-reduction ability because of the incorporation of MXene flakes. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 259 publications
(91 citation statements)
references
References 64 publications
1
88
0
1
Order By: Relevance
“…The kinetic constant k of the above catalytic reduction reaction was calculated to be 0.16597s −1 and 0.00401 s −1 , respectively. The kinetic constant k could intuitively reflect the speed of the catalytic reduction reaction [58][59][60][61][62][63][64][65]. Obviously, PEI/PCL@PdNPs catalytically reduced 4-NP faster.…”
Section: Catalytic Performance Of Pei/pcl@pdnps Compositesmentioning
confidence: 99%
“…The kinetic constant k of the above catalytic reduction reaction was calculated to be 0.16597s −1 and 0.00401 s −1 , respectively. The kinetic constant k could intuitively reflect the speed of the catalytic reduction reaction [58][59][60][61][62][63][64][65]. Obviously, PEI/PCL@PdNPs catalytically reduced 4-NP faster.…”
Section: Catalytic Performance Of Pei/pcl@pdnps Compositesmentioning
confidence: 99%
“…Thus, present obtained composite hydrogels demonstrated a new clue for the design of self-assembled nanomaterials and organized composites. [54][55][56][57][58][59][60][61][62][63][64][65]…”
Section: Preparation and Catalytic Performance Of The Aunp/t-g Hydrogelmentioning
confidence: 99%
“…2,5,16 It has been reported that another family of 2D materials, transition metal carbides and nitrides (MXenes) can be used as SERS substrates [10][11][12][13]15 and for other applications. [17][18][19] Both the structure and electronic properties of MXene-Ti 3 C 2 T x were largely affected by the functional groups on the MXenes where X = -F, -O and -OH. 11,[20][21][22] Density functional theory (DFT) simulations have reported on the band diagrams and the optical properties of monolayer MXenes; however, the obtained values are yet to be verified by experimental measurements.…”
mentioning
confidence: 99%